Impact of model structure on radionuclide transport in urban stormwater. (February 2023) - Mikelonis, Anne; Shireman, Jonathan; Ratliff, Katherine
Abstract: This paper compared simulation results from different SWMM model constructions after radiological contamination from a hypothetical dirty bomb. The model constructions included a utility-provided combined sewer model, a high-resolution mesh surface flow model, and a hybrid of the two. The models were run under three different rainfall configurations including a 3-h event, a 24-h event, and a 24-h event with 48 h of drainage to investigate the influence that model structure had on transport of 137 Cs. Model structure was found to impact the contaminant loading of the stormwater model from the air modeling. It was also found to impact the amount of contaminant washoff (high resolution modeling produced more washoff), flow of contamination through outfalls (more contamination through outfalls connected to underground pipes), and 137 Cs levels per pipe. The implications of these findings are that few stormwater models are considered ready to aid in response and recovery as originally designed. Highlights: Model structure impacts predicted radionuclide transport through stormwater system. Typical stormwater model construction requires modification for emergency response. High resolution modeling helps visualize pollutant drainage pathways. Infrastructure connections are necessary to simulate outfall pollutant discharges.